Structural insights into the efficient CO2‐reducing activity of an NAD‐dependent formate dehydrogenase from Thiobacillus sp. KNK65MA. (1st February 2015) - Choe, Hyunjun; Ha, Jung Min; Joo, Jeong Chan; Kim, Hyunook; Yoon, Hye‐Jin; Kim, Seonghoon; Son, Sang Hyeon; Gengan, Robert M.; Jeon, Seung Taeg; Chang, Rakwoo; Jung, Kwang Deog; Kim, Yong Hwan; et al.
<x xml:space="preserve">Abstract</x> CO2 fixation is thought to be one of the key factors in mitigating global warming. Of the various methods for removing CO2, the NAD‐dependent formate dehydrogenase from Candida boidinii (CbFDH) has been widely used in various biological CO2‐reduction systems; however, practical applications of CbFDH have often been impeded owing to its low CO2‐reducing activity. It has recently been demonstrated that the NAD‐dependent formate dehydrogenase from Thiobacillus sp. KNK65MA (TsFDH) has a higher CO2‐reducing activity compared with CbFDH. The crystal structure of TsFDH revealed that the biological unit in the asymmetric unit has two conformations, i.e. open (NAD+‐unbound) and closed (NAD+‐bound) forms. Three major differences are observed in the crystal structures of TsFDH and CbFDH. Firstly, hole 2 in TsFDH is blocked by helix α20, whereas it is not blocked in CbFDH. Secondly, the sizes of holes 1 and 2 are larger in TsFDH than in CbFDH. Thirdly, Lys287 in TsFDH, which is crucial for the capture of formate and its subsequent delivery to the active site, is an alanine in CbFDH. A computational simulation suggested that the higher CO2‐reducing activity of TsFDH is owing to its lower free‐energy barrier to CO2 reduction than in CbFDH.